Sustainable Wildlife Management - Khan Perveen, Farzana (Environmental Sciences, 2023)
Wildlife includes undomesticated native species of animals and plants of a region and all organisms that grow or live wild in an area without being introduced by humans. All game species, both birds and mammals, that are hunted for food and sport are also included. They can be found in all ecosystems and are protected for many reasons. Many national and international organizations, including the World Wildlife Fund, Conservation International, the Wildlife Conservation Society, and the United Nations, are working to support global animal and habitat conservation, working with governments to establish and protect public lands such as national parks and wildlife refuges, helping to draft legislation to protect various species, and working with law enforcement to prosecute wildlife crimes such as trafficking, illegal hunting, and poaching.